Collaborative Governance Dalam Menangulangi Banjir di Kota Sungai Penuh (Universitas 17 Agustus 1945 Surabaya, 2023)
Sungai Penuh City consists of several sub-districts that are prone to flooding every year, namely Tanah Kampung District, Hamparan Rawang District, and Kota Baru District. Therefore, the Regional Disaster Management Agency (BPBD) for the City of Sungai Penuh is trying to deal with the flood. The purpose of this study is to analyze and explain how collaborative governance is in tackling flooding in the City of Sungai penuh. The type of research used is qualitative research with descriptive methods by prioritizing research aids, namely observation, interviews and documentation. Informants in this study are stakeholders who are directly involved in tackling floods in these 3 sub-districts consisting of the Chairperson of the Regional Disaster Management Agency for the City of Sungai Penuh, Head of the Public Works and Spatial Planning Office for Cipta Karya (PUPR) for the City of Sungai Penuh, Head of the Housing and Settlements Service. Sungai Penuh City and Communities affected by flooding. This study uses collaborative governance theory to see the extent to which the achievements and weaknesses of flood control have been achieved. The results of this study have not fully gone well due to the fact that maximum collaboration has not been created between related agencies appointed by the Mayor of Sungai Penuh City in flood prevention. In the future, it is hoped that the BPBD of SungaiFull City can cooperate with other agencies in dealing with floods. In addition, the BPBD of Sungai Penuh City must continue to provide outreach and simulations, especially during the rainy season so that the people of Sungai Penuh City can prepare themselves from an early age.